2021
DOI: 10.18231/j.ijmmtd.2021.017
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility of clinically significant candida species by disk diffusion method

Abstract: Antifungal susceptibility of candida. To perform antifungal susceptibility testing on candida isolates by disk diffusion method & study its susceptibility pattern. The present study was conducted in the department of Microbiology in a tertiary care hospital in Hyderabad from January 2013 to June 2014, with prior approval of the Institutional Ethics Committee. The present study was designed to perform antifungal susceptibility test on Candida isolates by Disk Diffusion Method and study its susceptibility p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“… 90 Likewise, related studies also reported a comparable prevalence to our findings. 91 , 92 In contrast to our study, which showed that C. glabrata is the most predominant non– albicans (NAC) species, a study reported that C. tropicalis was the most prevalent NAC species in clinical isolates obtained from a hospital in Hyderabad. 93 Combining the prevalence of the other unidentified NAC species and the NAC (identified) species, we show that NAC has a greater prevalence than C. albicans , and other studies have corroborated this observation, 94 , 95 making the emergence of NAC species of important concern.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“… 90 Likewise, related studies also reported a comparable prevalence to our findings. 91 , 92 In contrast to our study, which showed that C. glabrata is the most predominant non– albicans (NAC) species, a study reported that C. tropicalis was the most prevalent NAC species in clinical isolates obtained from a hospital in Hyderabad. 93 Combining the prevalence of the other unidentified NAC species and the NAC (identified) species, we show that NAC has a greater prevalence than C. albicans , and other studies have corroborated this observation, 94 , 95 making the emergence of NAC species of important concern.…”
Section: Discussioncontrasting
confidence: 67%
“…This indicates that there are diverse Candida species that are harbored in the vagina of women apart from the common species such as C. albicans, C. krusei, C. glabrata, C. tropicalis , and C. parapsilosis . The significance of this finding is that other unidentified Candida species, such as the recently trending C. dubliniensis , 92 for which resistance to fluconazole has also been identified 96–98 may substitute for C. albicans under favorable conditions.…”
Section: Discussionmentioning
confidence: 83%